Análise teórico: experimental de um concentrador solar tipo Fresnel Linear - Scalco, Patricia (Universidade do Vale do Rio dos Sinos, 2025)
Solar radiation, an abundant and renewable source, can be harnessed through solar concentrators, which direct and concentrate incident radiation into small areas, converting it into heat for electricity generation or to supply industrial processes requiring medium to high temperatures. One of the technologies that apply this concept is the Linear Fresnel Reflector (LFR), which uses parallel rows of flat (or slightly curved) mirrors that move throughout the day following the movement of the Sun. Solar radiation strikes the mirrors and is reflected to an absorber, where the radiation is converted into thermal energy. In this context, this thesis presents a theoretical and experimental analysis of the performance of an LFR system with a trapezoidal cavity receiver, installed at the Renewable Sources Laboratory of the University of Vale do Rio dos Sinos (UNISINOS). The study was structured in three main stages: geometric and analytical modeling, thermal analysis of the receiver, and experimental validation. The first step involved characterizing the mirror array and receiver, applying the gap angle concept to redistribute the mirror rows to minimize blocking and shading losses. Subsequently, a thermal model was developed to simulate heat transfer in the receiver: heat balances were applied to each of the surfaces involved in the heat exchange, properties of the Paratherm HE thermal fluid, conduction, convection, and radiation losses. Subsequently, experimental tests were conducted on different days and flow rates, enabling comparison with theoretical results. The analysis revealed that, although the thermal model accurately predicts thermal trends, discrepancies occur due to operational instabilities and limitations in experimental control. Furthermore, the results showed that the trapezoidal cavity receiver achieved an optical efficiency of 77% and a CAP of 0.24, values higher than those obtained with the CPC combined with the evacuated tube (63% and CAP of 0.10). Mirror redistribution using the gap angle criterion increased efficiency to 89%, albeit with a smaller angular tolerance. Experimental tests confirmed the influence of operating conditions and thermal losses, while the theoretical model adequately reproduced the receiver's behavior, highlighting the importance of convection and radiation losses at high temperatures.
Keywords: Refletor Fresnel linear; Análise teórico-experimental; Modelo óptico; Modelo térmico; Análise experimental; Linear Fresnel reflector; Theoretical-experimental analysis; Optical model; Thermal model; Experimental analysis; ACCNPQ::Engenharias::Engenharia Mecânica